District Heating Rehabilitation in Russia : The hydro-ejector system's replacement with the plate heat exchanger - Vuorensola, Jussi (Oulun ammattikorkeakoulu, 2015)
This thesis has two assigners. The first one is Karelia institute, which wanted more information about the hydro-ejector's functions and Russian heating norms. Besides of that Jupra Oy, which wanted to find out about co-operation possibilities between different counterparts in the Russian Heating sector. The com-pany also wanted to make sure, that it is possible to replace the ejector system with a plate heat ex-changer system. Karelia institute works closely together with Oulu University of Applied Sciences, so it was natural to me choose to help them with this task and Jupra Oy functioned as a financier of this thesis. Background knowledge for this thesis was achieved with the assistance of a lecture of Oulu UAS Veli-Matti Mäkelä and multiple professors and lectures of Petrozavodsk State University. Research was inter-national and was partly made in Finland and partly in the Russian Federation. Methods of this thesis are based on acquiring information from literature, innovations and unofficial inter-views of local experts and officials. As a result this thesis gives common information about a district heating, market relationships, views of the energy policy, the tariff structure of the Russian Federation, the physical theory of the ejector, meas-urement methods of the ejector in the Russian Federation, the physical theory of the plate heat exchang-er, the plate heat exchanger designing and introduces how to replace the ejector system with the plate heat exchanger system. There are plenty of options to develop this work even further. Convergence work with different counter-parts needs constant initiatives, mathematic calculation programs can be made with base on this thesis, further research on laws and norms can be done. This inspirational work gives also keys, which can lead to the new innovations.